DEVELOPING HYBRID MEDIA INSTALLATION GAME IN TAMAN GAJAH TUNGGAL - Agatha Maisie Tjandra; Lalitya Talitha Pinasthika; Rangga Winantyo (Universitas Multimedia Nusantara, 2020)
In the recent five years, City parks have been developing rapidly in urban cities in Indonesia. Built in 2007, Taman Gajah Tunggal is one of the city parks located in Tangerang. This park is situated at The Center of Tangerang City on the edge of Cisadane River. Like many public spaces in Indonesia, this park has littering issues by visitors’ lack of care. This re- search is offered to develop social marketing by using a digital game for gaining awareness of Taman Gajah Tunggal’s visitors age 17-30 years old about littering issues. This paper focused on developing the prototyping process in iteration design method by using a digital game to suggest possibilities design for future development interactive installation design in public space which can bring a new experience.